Ozone Treatment Improves the Texture of Strawberry Fruit during Storage - Tomasz Piechowiak; Dagmara Migut; Radosław Józefczyk; Maciej Balawejder (MDPI AG, 2022)
The major aim of this study was to check whether a cyclic ozonation process will affect the preservation of the texture of strawberries stored at room temperature. Strawberry fruit was stored for 3 days at room temperature and ozonated with gaseous ozone at a concentration of 10 and 100 ppm for 30 min, every 12 h of storage. Research showed that the ozonation process inhibited the texture deterioration of the fruit during storage. The positive effect of ozone was directly related to the inhibition of the activity of enzymes involved in the degradation of the fruit cell walls, as well as indirectly from the improved energy metabolism of the fruit. The higher level of energy charge corresponded to the higher resistance of ozonated fruit to abiotic stress, leading to the maintenance of the integrity of cell membranes and, consequently, to maintaining good hardness of the fruit throughout the storage period.